The Application of Lean Six Sigma on Strapping and Barband Tray Production Lines: A Case Study at FBS Company - Sendi, Ezzat Omar (2006)
The purpose of this dissertation is to identify and understand prevalent industrial production processes that can benefit from the implementation of a Lean Six Sigma approach and to facilitate its implementation on a realistic level in the production market through the use of a case study. The tools used included the application of the Cause and Effect Diagram as well as various problem solving techniques and quality tools that can be applicable over a large segment of production facilities to improve product quality and production time while reducing waste and increasing factory profits and productivity.